2015
DOI: 10.1038/srep11274
|View full text |Cite
|
Sign up to set email alerts
|

A novel male sterility-fertility restoration system in plants for hybrid seed production

Abstract: Hybrid seeds are used for stimulated crop production, as they harness heterosis. The achievement of complete male-sterility in the female-parent and the restored-fertility in F1-hybrids are the major bottlenecks in the commercial hybrid seed production. Here, we report a male sterility–fertility restoration system by engineering the inmost nutritive anther wall layer tapetum of female and male parents. In the female parent, high–level, and stringent expression of Arabidopsis autophagy–related gene BECLIN1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Autophagy plays a dispensable role in regular reproductive development, including tapetal PCD, in Arabidopsis, because almost all isolated autophagy-defective (atg) mutants can complete their life cycle under normal conditions (Yoshimoto 2012). Intriguingly, the occurrence of male sterility in a transgenic tobacco line overexpressing Arabidopsis AtATG6/BECLIN1 in the tapetum cells (Singh et al 2010(Singh et al , 2015 suggested that excessive autophagy might accelerate 3 tapetum cell death and lead to abortion of microsporogenesis in tobacco. Nevertheless, the rice autophagy null mutant OsATG7 showed a defect in tapetum cell degradation and sporophytic male sterility (Kurusu et al 2014;Hanamata et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy plays a dispensable role in regular reproductive development, including tapetal PCD, in Arabidopsis, because almost all isolated autophagy-defective (atg) mutants can complete their life cycle under normal conditions (Yoshimoto 2012). Intriguingly, the occurrence of male sterility in a transgenic tobacco line overexpressing Arabidopsis AtATG6/BECLIN1 in the tapetum cells (Singh et al 2010(Singh et al , 2015 suggested that excessive autophagy might accelerate 3 tapetum cell death and lead to abortion of microsporogenesis in tobacco. Nevertheless, the rice autophagy null mutant OsATG7 showed a defect in tapetum cell degradation and sporophytic male sterility (Kurusu et al 2014;Hanamata et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, precise control over pollen fertility in the female parent is practically needed, and several approaches have been explored (Singh et al. ). Cytoplasmic male sterility (CMS) is an effective method and has been exploited in hybrid breeding of some crop species (Touzet and Meyer , Islam et al ); yet, hybrids obtained through CMS line may be sterile, which restricts the economic benefits of the hybrid crops where the desired agricultural products are seeds (Singh et al.…”
mentioning
confidence: 99%
“…Cytoplasmic male sterility (CMS) is an effective method and has been exploited in hybrid breeding of some crop species (Touzet and Meyer , Islam et al ); yet, hybrids obtained through CMS line may be sterile, which restricts the economic benefits of the hybrid crops where the desired agricultural products are seeds (Singh et al. ), or limits the sexual reproduction of these scarce hybrids. Consequently, it is extremely critical to exploit resources with fertility restoring gene and restore fertility in hybrid (Bentolila et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations